2010
DOI: 10.1111/j.1468-1331.2010.03225.x
|View full text |Cite
|
Sign up to set email alerts
|

Does apolipoprotein E genotype modify the clinical expression of ALS?

Abstract: Our results suggest that ApoE genotype does not modify clinical course of sporadic ALS, in stark contrast to the influence of ApoE genotype on the disease course of AD and other neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…The APOE genotypes do not seem to influence the risks of Huntington disease 89 nor amyotrophic lateral sclerosis. 90 …”
Section: Apoe Genotypes Ad and Cognitionmentioning
confidence: 99%
“…The APOE genotypes do not seem to influence the risks of Huntington disease 89 nor amyotrophic lateral sclerosis. 90 …”
Section: Apoe Genotypes Ad and Cognitionmentioning
confidence: 99%
“…It was suggested that the ε4 allele has a deleterious effect on ALS survival (271, 272) and association with younger age at ALS onset (273), but these findings were not subsequently confirmed (274). ApoE is a widely distributed, well-characterized cholesterol transport protein that circulates in the plasma after being synthesized by the liver, spleen, and kidneys (275).…”
Section: Modifier Genes Associated With Sals and Oxidative Stressmentioning
confidence: 99%
“…In addition to the aforementioned genetic mutations, a number of other genetic mutations and polymorphisms have been identified to be associated with sporadic ALS (Chen et al, 2013). Studies on the influence of apoE genotype on ALS have provided conflicting results (Jawaid et al, 2011; Praline et al, 2011). A recent study in a large cohort of French patients with sporadic ALS (n=1,482) and matched controls (n=955) found that APOE -ε4 allele was associated with an increased risk of bulbar-onset ALS in men (Praline et al, 2011).…”
Section: Genetic Clinical and Experimental Evidence For Protective Ementioning
confidence: 99%